Technological Learning and Technological Innovation Creation: An Empirical Analysis of Biotechnology R&D Teams - Hao-Chen Huang (Journal of Engineering Science and Technology Review, 2013)
Resource-based perspective was used to relate the technological learning processes and transformative capacity to technological innovation using a sample of 193 biotechnology R&D teams. Structural equation modeling was used to conduct confirmatory factor analysis (CFA) to evaluate the measurement model, while hierarchical regression analysis was used to test the hypotheses. As expected, the technological learning processes were positively associated with technological innovation. Further, the transformative capacity of R&D team was also crucial. The transformative capacity is a powerful approach to maintaining, transforming, and reactivating knowledge for biotechnology firms. It positively moderated the association between external learning and technological innovation.